2007
DOI: 10.3141/2024-14
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Seasonal Time Series Models for Forecasting Short-Term Traffic Flow

Abstract: Conventionally, most traffic forecasting models have been applied in a static framework in which new observations are not used to update model parameters automatically. The need to perform periodic parameter reestimation at each forecast location is a major disadvantage of such models. From a practical standpoint, the usefulness of any model depends not only on its accuracy but also on its ease of implementation and maintenance. This paper presents an adaptive parameter estimation methodology for univariate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(80 citation statements)
references
References 5 publications
0
78
0
2
Order By: Relevance
“…It is worth mentioning that it would be interesting to check the performance of a dynamic linear approach in order to overcome the limitations of a static model such as SARIMA. Some authors have found several advantages and improvements with the use of adaptive linear models (Shekhar and Williams, 2008;Guo et al, 2014Guo et al, , 2015.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…It is worth mentioning that it would be interesting to check the performance of a dynamic linear approach in order to overcome the limitations of a static model such as SARIMA. Some authors have found several advantages and improvements with the use of adaptive linear models (Shekhar and Williams, 2008;Guo et al, 2014Guo et al, , 2015.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The SARIMA model improves the predictive accuracy via drawing the periodicity of the traffic data. It constructs the independent variables using the traffic data in the past several intervals together with the historical data in the same intervals in the last week [7], [19]. SARIMA not only provides the short-term causality but also the long-term change rule of traffic state.…”
Section: Problem Statement and Related Workmentioning
confidence: 99%
“…3) SARIMA: The SARIMA model is one of the stateof-the-art parametric techniques and has been successfully applied to the traffic prediction [7], [19], [27]. Through capturing the evident repeating pattern week by week of traffic flow data, the SARIMA introduces weekly dependence relations to the standard ARIMA model and improves the predictive accuracy.…”
Section: ) T-marsmentioning
confidence: 99%
See 2 more Smart Citations